TI_GERICHTE 32.2010.164 vom 12. Mai 2010 , UAI ha correttamente determinato l'ammontare della rendita spettante all'assicurata - TI Tribunale d'appello (2010)
UAI ha correttamente determinato l'ammontare della rendita spettante all'assicurata